2008
DOI: 10.1021/jf8007426
|View full text |Cite
|
Sign up to set email alerts
|

Water Distribution and Microstructure in Enhanced Pork

Abstract: Water characteristics and meat microstructure of NaHCO3-enhanced pork were compared with NaCl- and Na4O7P2-enhanced pork using low-field proton NMR relaxometry, advanced microscopy techniques, and traditional meat quality measurements. Porcine samples were enhanced at 4 degrees C for 48 h with sodium salts individually and in the following combinations: (i) 5% NaCl, (ii) 5% Na4O7P2, (iii) 3% NaHCO3, (iv) 5% NaCl and 5% Na4O7P2, (v) 5% NaCl and 3% NaHCO3, (vi) 5% Na4O7P2 and 3% NaHCO3, and (vii) 5% NaCl, 5% Na4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 28 publications
10
43
1
Order By: Relevance
“…However, CT, TM1, and TM2 did not differ from each other. These data confirm the synergistic effect of TM3, with positive results on pork characteristics, as evidenced by Bertram et al (2008). Phosphate salts and brines are used in depolymerized muscle fiber myosin filaments, and help dissociating the act-myosin complex, increasing the dissolved protein (Bertram et al, 2008).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, CT, TM1, and TM2 did not differ from each other. These data confirm the synergistic effect of TM3, with positive results on pork characteristics, as evidenced by Bertram et al (2008). Phosphate salts and brines are used in depolymerized muscle fiber myosin filaments, and help dissociating the act-myosin complex, increasing the dissolved protein (Bertram et al, 2008).…”
Section: Resultssupporting
confidence: 74%
“…These data confirm the synergistic effect of TM3, with positive results on pork characteristics, as evidenced by Bertram et al (2008). Phosphate salts and brines are used in depolymerized muscle fiber myosin filaments, and help dissociating the act-myosin complex, increasing the dissolved protein (Bertram et al, 2008). In addition, they capture the negatively charged metal ions, leaving the actual charges free to bind water molecules, thereby increasing the capacity of meat to retain water (Xiong, 2005).…”
Section: Resultssupporting
confidence: 69%
“…Some recent studies showed that bicarbonate compounds can be reduce by the drip loss and shear force, which improve the yield as well as phosphates. This effect could be explained because bicarbonates have higher buffering capacity and ionic strength than phosphates [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Bicarbonate compounds have evaluated as a phosphate replacer under the same conditions of heat treatment [10,11]. Scarce in formations are available about the effect of bicarbonate in comparison to phosphates under different conditions of heat treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the addition of 10 g/kg quinoa flour increased the WHC, WBA and cooking yield, which may be due to the absorption of water by the myofibrils, reducing the water loss during cooking (BERTRAM et al, 2008; Means (n = 3) with different letters in the same row are significantly different at 5%. Each value indicates the mean of the measurement ± standard error.…”
Section: Resultsmentioning
confidence: 93%